Guru dalam Perspektif Islam di Madrasah Aliyah Syekh Yusuf Sungguminasa Kabupaten Gowa: Teacher in Islamic Perspective at Madrasah Aliyah Sheikh Yusuf Sungguminasa, Gowa Regency - Qadri, Muhammad; Achruh, Andi; Rosdiana (CV. Kalimasada Group, 2023)
This research aims to determine the position of an educator (teacher) in Islam with a case study at Madrasah Aliyah Sheikh Yusuf Sungguminasa, Gowa Regency, South Sulawesi. This research used a descriptive qualitative approach to investigate the role of teachers from an Islamic perspective. The results showed that: (1) Madrasah Aliyah Sheikh Yusuf Sungguminasa Gowa Regency teachers are aware of their position in Islam as a source of scientific and spiritual guidance for students; (2) the role of teachers has a significant influence on the quality of education, because Islamic teachings encourage good performance when teachers view their duties as a noble profession; (3) Society respects teachers, with mastery of the four main competencies of pedagogical, social, professional, and personality being the main elements that influence their position. This study shows that educators can improve education standards and have a recognized status in society if they view their duties and competencies from an Islamic perspective.